Impact of errors in recorded compressed breast thickness measurements on volumetric density classification using volpara v1.5.0 software. Issue 6 (16th May 2016) - Waade, Gunvor Gipling; Highnam, Ralph; Hauge, Ingrid H. R.; McEntee, Mark F.; Hofvind, Solveig; Denton, Erika; Kelly, Judith; Sarwar, Jasmine J.; Hogg, Peter
Abstract : Purpose: Mammographic density has been demonstrated to predict breast cancer risk. It has been proposed that it could be used for stratifying screening pathways and recommending additional imaging. Volumetric density tools use the recorded compressed breast thickness (CBT) of the breast measured at the x‐ray unit in their calculation; however, the accuracy of the recorded thickness can vary. The aim of this study was to investigate whether inaccuracies in recorded CBT impact upon volumetric density classification and to examine whether the current quality control (QC) standard is sufficient for assessing mammographic density. Methods: Raw data from 52 digital screening mammograms were included in the study. For each image, the clinically recorded CBT was artificially increased and decreased in increments of 1 mm to simulate measurement error, until ±15% from the recorded CBT was reached. New images were created for each 1 mm step in thickness resulting in a total of 974 images which then hadvolpara density grade (VDG) and volumetric density percentage assigned. Results: A change in VDG was observed in 38.5% ( n = 20) of mammograms when applying ±15% error to the recorded CBT and 11.5% ( n = 6) was within the QC standard prescribed error of ±5 mm. Conclusions: The current QC standard of ±5 mm error in recorded CBT creates the potential for error in mammographic density measurement. This may lead to inaccurate classification of mammographic density. The current QC standard for assessing mammographic density should be reconsidered.